2016
DOI: 10.1111/jocn.13582
|View full text |Cite
|
Sign up to set email alerts
|

Continence care for people with dementia living at home in Europe: a review of literature with a focus on problems and challenges

Abstract: Aims and objectives. To report the findings of a review of literature relating to the continence care of community-dwelling people with dementia in Europe. Background. More than two-thirds of people with dementia live at home, and many experience continence problems. Incontinence is a significant contributor towards institutionalisation. Care and support is often inadequate or inappropriate, and guidelines are lacking. This represents a failure to respect the human rights and dignity of this group. Design. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Other major risk factors that were previously reported for urinary and fecal incontinence among people with dementia include psychotropic medication, 26 depression and building environment. 27 In the present study, the effect of psychotropics could not be determined because of the high prevalence of psychotropic prescriptions. However, the prevalence of depression noted on the medical record was low, and depression cannot account for the large variation in the prevalence of incontinence.…”
Section: Discussionmentioning
confidence: 82%
“…Other major risk factors that were previously reported for urinary and fecal incontinence among people with dementia include psychotropic medication, 26 depression and building environment. 27 In the present study, the effect of psychotropics could not be determined because of the high prevalence of psychotropic prescriptions. However, the prevalence of depression noted on the medical record was low, and depression cannot account for the large variation in the prevalence of incontinence.…”
Section: Discussionmentioning
confidence: 82%
“…Good management of continence makes life easier for carers, but care and support is often inadequate or inappropriate and guidelines are lacking. 6 The loss of bladder and bowel control is associated with old age and frailty, as is dementia, but incontinence is not inevitable in dementia and every person with dementia is entitled to the same continence assessment, diagnosis and treatment as any other patient. In the community they should be referred to the continence nurse and/ or urology specialist as required.…”
Section: Continencementioning
confidence: 99%
“…Several studies have found that toileting difficulties including incontinence have a major impact on quality of life (Stenzelius, Mattiasson, Hallberg, & Westergren, 2004;Teunissen et al, 2004), mental health and social participation (Bedretdinova, Fritel, Zins, & Ringa, 2016;Felde, Bjelland, & Hunskaar, 2012;Stenzelius et al, 2004). Especially when combined with dementia, incontinence may cause great stress for both the individual and its caregivers (Finne-Soveri et al, 2008;Gove et al, 2016;Grant et al, 2013;Thomas et al, 2004). In a review recently published, great concern was expressed about the lacking knowledge on toileting difficulties in community-dwelling older European people with dementia (Gove et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Especially when combined with dementia, incontinence may cause great stress for both the individual and its caregivers (Finne‐Soveri et al, ; Gove et al, ; Grant et al, ; Thomas et al, ). In a review recently published, great concern was expressed about the lacking knowledge on toileting difficulties in community‐dwelling older European people with dementia (Gove et al, ). Among community‐dwelling older people in Norway receiving formal in‐home care, the prevalence of dementia is reported to be 42% (Wergeland et al, ), but information about the prevalence of toileting difficulties and whether the prevalence of toileting difficulties is higher in this group compared to those without dementia has been lacking.…”
Section: Introductionmentioning
confidence: 99%